On the heat stability of amyloid-based biological activity: insights from thermal degradation of insulin fibrils. - Weronika Surmacz-Chwedoruk (Public Library of Science (PLoS), 2014)
Formation of amyloid fibrils in vivo has been linked to disorders such as Alzheimer's disease and prion-associated transmissible spongiform encephalopathies. One of the characteristic features of amyloid fibrils is the high thermodynamic stability relative both to native and disordered states which is also thought to underlie the perplexingly remarkable heat resistance of prion infectivity. Here, we are comparing high-temperature degradation of native and fibrillar forms of human insulin. Decomposition of insulin amyloid has been studied under helium atmosphere and in the temperature range from ambient conditions to 750°C using thermogravimetry and differential scanning calorimetry coupled to mass spectrometry. While converting native insulin into amyloid does upshift onset of thermal decomposition by ca. 75°C, fibrils remain vulnerable to covalent degradation at temperatures below 300°C, as reflected by mass spectra of gases released upon heating of amyloid samples, as well as morphology and infrared spectra of fibrils subjected to incubation at 250°C. Mass spectra profiles of released gases indicate that degradation of fibrils is much more cooperative than degradation of native insulin. The data show no evidence of water of crystallization trapped within insulin fibrils. We have also compared untreated and heated amyloid samples in terms of capacity to seed daughter fibrils. Kinetic traces of seed-induced insulin fibrillation have shown that the seeding potency of amyloid samples decreases significantly already after exposure to 200°C, even though corresponding electron micrographs indicated persisting fibrillar morphology. Our results suggest that amyloid-based biological activity may not survive extremely high temperature treatments, at least in the absence of other stabilizing factors.